Problem behavior in young children referred with language difficulties: Relations to language and intentional communication. (January 2020) - Jansen, Rianne; Maljaars, Jarymke; Verhappen, Anouk; Zink, Inge; Steyaert, Jean; Noens, Ilse
Background and aims: This exploratory study aims to examine the relative contribution of language and intentional communication to internalizing and externalizing problem behavior. Methods: Twenty-nine Dutch-speaking children (age range 24–46 months) referred with language difficulties participated in this study. For the majority of children, these early language difficulties appeared to be part of a broader neurodevelopmental disorder, mainly autism spectrum disorder. Parent ratings on the Achenbach Child Behavior Checklist 1½–5 were predicted from children's language level and intentional communicative abilities, the latter being assessed by both parent report and direct observation. In all series of hierarchical regression analyses, chronological age and nonverbal mental age were included as covariates. Results: Parents commonly reported withdrawal, emotionally reactive behavior, attention problems, and aggressive behavior. Parent-rated intentional communication was the most important predictor of internalizing problem behavior and played an important role in the prediction of aggressive behavior as well. However, chronological age and/or nonverbal mental age also predicted parent-rated levels of externalizing problem behavior, especially attention problems. Conclusions: The relation between language difficulties and problem behavior may be influenced by maturation and children's ability to communicate intentionally. Implications: Language proficiency should, therefore, be independently assessed from children's intentional communicative abilities which, in turn, may differ across contexts.